2022
DOI: 10.1061/(asce)gt.1943-5606.0002645
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Pipe-Jacking Forces Using a Bayesian Updating Approach

Abstract: An accurate estimation of the jacking forces likely to be experienced during microtunnelling is a key design concern for the design of pipe segments, the location of intermediate jacking stations and the efficacy of the pipe jacking project itself. This paper presents a Bayesian updating approach for the prediction of jacking forces during microtunnelling. The proposed framework is applied to two pipe jacking case histories completed in the UK including a 275 m drive in silt and silty sand and a 1237 m drive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…et al [14][15][16] thoroughly examined the mechanism of soil disturbance, additional thrust on the excavation surface, friction of the pipe jacking machine with the soil, friction of the subsequent pipeline with the soil, and grouting pressure. Sheil et al's [17] investigation into the process by which pipe jacking disturbs the soil led to the development of a formula for predicting the jacking force of rectangular jacking pipes with large cross sections. Ma et al [18,19] suggested a pipe-soil contact model and its associated computing method for rectangular jacking pipe.…”
Section: Of 15mentioning
confidence: 99%
“…et al [14][15][16] thoroughly examined the mechanism of soil disturbance, additional thrust on the excavation surface, friction of the pipe jacking machine with the soil, friction of the subsequent pipeline with the soil, and grouting pressure. Sheil et al's [17] investigation into the process by which pipe jacking disturbs the soil led to the development of a formula for predicting the jacking force of rectangular jacking pipes with large cross sections. Ma et al [18,19] suggested a pipe-soil contact model and its associated computing method for rectangular jacking pipe.…”
Section: Of 15mentioning
confidence: 99%
“…Bayesian methods have gained significant attention in geotechnical engineering. They been employed to assess the probability of slope failure [23][24][25][26][27] and to predict tunnel Geotechnics 2024, 4 383 deformation [28][29][30][31][32], excavation movements [33][34][35][36][37], pipe-jacking forces [38], and pile driveability [39]. The advantages of Bayesian methods in geotechnical engineering include the ability to integrate multiple sources of information, such as expert opinions, field data, and laboratory tests, to reduce uncertainties and improve decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Since its application in the Northern Pacific Road laying project in the United States, the pipe jacking method is gradually attracting elevated levels of attention and is becoming an important method for constructing underground engineering. With a developmental history of over 200 years, it is quite mature and has recently been successfully applied in the context of practical engineering, such as in tunnels, rainwater box culverts, and underground passages [1][2][3]. In view of previous studies, researchers have conducted many studies on the safety and efficiency of pipe jacking engineering.…”
Section: Introductionmentioning
confidence: 99%